2019
DOI: 10.1371/journal.pntd.0007047
|View full text |Cite
|
Sign up to set email alerts
|

Dengue and chikungunya among outpatients with acute undifferentiated fever in Kinshasa, Democratic Republic of Congo: A cross-sectional study

Abstract: BackgroundPathogens causing acute fever, with the exception of malaria, remain largely unidentified in sub-Saharan Africa, given the local unavailability of diagnostic tests and the broad differential diagnosis.MethodologyWe conducted a cross-sectional study including outpatient acute undifferentiated fever in both children and adults, between November 2015 and June 2016 in Kinshasa, Democratic Republic of Congo. Serological and molecular diagnostic tests for selected arboviral infections were performed on blo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
39
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 54 publications
3
39
2
Order By: Relevance
“…Given the low number of positive cases, a rigorous assessment of the performance of the dengue rapid diagnostic tests was not possible. The relatively poor correlation in IgG results between the dRDT and the ELISA is consistent with a study of febrile outpatients conducted in the Democratic Republic of Congo, which showed 2.5% IgG positivity by dRDT and 34.0% positivity by ELISA with an estimated sensitivity of 7.6% [32]. Our results do highlight the urgent need for better diagnostics and management algorithms for children with acute febrile illness.…”
Section: Discussionsupporting
confidence: 86%
“…Given the low number of positive cases, a rigorous assessment of the performance of the dengue rapid diagnostic tests was not possible. The relatively poor correlation in IgG results between the dRDT and the ELISA is consistent with a study of febrile outpatients conducted in the Democratic Republic of Congo, which showed 2.5% IgG positivity by dRDT and 34.0% positivity by ELISA with an estimated sensitivity of 7.6% [32]. Our results do highlight the urgent need for better diagnostics and management algorithms for children with acute febrile illness.…”
Section: Discussionsupporting
confidence: 86%
“…Worldwide, extensive variations in the seroprevalence of Flaviviruses are reported, the lowest are in African countries (between 12 and 50%) and Asia (25%). Among Latin America countries the prevalence reaches approximately 70% [ 25 , 33 – 38 ]. On the other hand, the prevalence of ZIKV it is more prominent where it caused major epidemics, such as in French Polynesia (66%) and Yap Islands (73%) [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a place like Kinshasa, where dengue is rarely reported [21][22][23][24] and chikungunya and yellow fever cause sporadic outbreaks [16,18,41], we didn't expect to nd such high Aedes densities. The observed densities are comparable to the ones of other African settings: south-eastern Tanzania has a HI of 4.9 -6.6, CI of 14.6-18.9 [42]; Burkina Faso a HI of 70, CI of 35 and BI of 10 [43]; north-west Ethiopia a HI of 25.5, CI of 32.9 and BI of 48.4 [44]; Mozambique a CI of 22 [45]; and Angola a HI of 4.3 -27.9, CI of 2.1-9.3 and BI of 5.8-42.2 [46].…”
Section: Discussionmentioning
confidence: 99%